B-cell receptor-driven MALT1 activity regulates MYC signaling in mantle cell lymphoma - Dai, Beiying; Grau, Michael; Juilland, Mélanie; Klener, Pavel; Höring, Elisabeth; Molinsky, Jan; Schimmack, Gisela; Aukema, Sietse M; Hoster, Eva; Vogt, Niklas; Staiger, Annette M; Erdmann, Tabea; et al. (Blood, 2017)
Mantle cell lymphoma (MCL) is a mature B-cell lymphoma characterized by poor clinical outcome. Recent studies revealed the importance of B-cell receptor (BCR) signaling in maintaining MCL survival. However, it remains unclear which role MALT1, an essential component of the CARD11-BCL10-MALT1 complex that links BCR signaling to the NF-κB pathway, plays in the biology of MCL. Here we show that a subset of MCLs is addicted to MALT1, as its inhibition by either RNA or pharmacologic interference induced cytotoxicity both in vitro and in vivo. Gene expression profiling following MALT1 inhibition demonstrated that MALT1 controls an MYC-driven gene expression network predominantly through increasing MYC protein stability. Thus, our analyses identify a previously unappreciated regulatory mechanism of MYC expression. Investigating primary mouse splenocytes, we could demonstrate that MALT1-induced MYC regulation is not restricted to MCL, but represents a common mechanism. MYC itself is pivotal for MCL survival because its downregulation and pharmacologic inhibition induced cytotoxicity in all MCL models. Collectively, these results provide a strong mechanistic rationale to investigate the therapeutic efficacy of targeting the MALT1-MYC axis in MCL patients.
Keywords: buněčná smrt; nádorové buněčné linie; signální transdukce; Neoplasm Proteins; protein MALT1; protoonkogenní proteiny c-myc; nádorové proteiny; heterografty; regulace genové exprese u nádorů; Proto-Oncogene Proteins c-myc; NF-kappa B; kaspasy; Signal Transduction; Mice; Cell Line, Tumor; Caspases; Cell Death; Lymphoma, Mantle-Cell; zvířata; Humans; Gene Expression Regulation, Neoplastic; receptory antigenů B-buněk; viabilita buněk; Cell Survival; Mucosa-Associated Lymphoid Tissue Lymphoma Translocation 1 Protein; myši; lymfom z plášťových buněk; Receptors, Antigen, B-Cell; Heterografts; lidé; Animals